Research on the Influence of Metamaterials on Single Photon LiDAR - Hu, Yingying; Xu, Duoduo; Zhou, Zehui; Zhao, Tianqi; Shi, Yan; Tian, Ying; Xu, Rui; Chen, Yi (Frontiers in Physics, 2020)
Single photon light detection and ranging (LiDAR) has the advantages of high angle and distance resolution, great concealment, a strong anti-active jamming capability, small volume, and light mass, and has been widely applied in marine reconnaissance, obstacle avoidance, chemical warfare agent detection, and navigation. With the rapid development of metamaterials, the performance of a single photon LiDAR system would be improved by optimizing the core devices in the system. In this paper, we first analyzed the performance index of the single photon LiDAR and discovered the potential of metamaterials in improving the system performance. Then, the influence of metamaterials on the core devices of the single photon LiDAR were discussed, including lasers, scanning devices, optical lenses, and single photon detectors. As a result, we have concluded that through effective light field modulation, metamaterial technology might enhance the performance innovation of the single photon LiDAR.